Comparative Analysis of Outcomes in Medicare-Eligible Patients with a Hospital Stay Less than Two-Midnights versus Longer Length of Stay following Total Knee Arthroplasty: Implications for Inpatient-Outpatient Designation - Singh, Vivek; Lygrisse, Katherine A.; Macaulay, William; Slover, James D.; Schwarzkopf, Ran; Long, William J. (The Journal of Knee Surgery, 2021)
The Centers for Medicaid and Medicare Services (CMS) removed primary total knee arthroplasty (TKA) from the inpatient-only list in January 2018. This study aims to compare outcomes in Medicare-aged patients who underwent primary TKA and had an in-hospital stay spanning less than two-midnights to those with a length of stay greater than or equal to two-midnights. We retrospectively reviewed 4,138 patients ages ≥65 who underwent primary TKA from 2016 to 2020. Two cohorts were established based on length of stay (LOS), those with an LOS <2 midnights were labeled outpatient and those with an LOS ≥2 midnights were labeled inpatient as per CMS designation. Demographic, clinical data, knee injury and osteoarthritis outcome score for joint replacement (KOOS, JR), and veterans RAND 12 physical and mental components (VR-12 PCS & MCS) were collected. Demographic differences were assessed with Chi-square and independent sample t-tests. Clinical data and KOOS, JR and VR-12 PCS and MCS scores were compared by using multilinear regression analysis, controlling for demographic differences. There were 841 (20%) patients with a LOS < 2 midnights and 3,297 (80%) patients with a LOS ≥ 2 midnights. Patients with a LOS < 2 midnights were significantly younger (71.70 vs. 73.06; p < 0.001), more likely male (42.1 vs. 25.7%; p < 0.001), Caucasian (68.8 vs. 57.7%; p <0.001), have lower BMI (30.80 vs. 31.92; p < 0.001), Charlson Comorbidity Index (CCI; 4.62 vs. 4.96; p < 0.001), and American Society of Anesthesiologists (ASA) class II or higher (p < 0.001). These patients were more likely to be discharged home compared to patients with LOS ≥ 2 midnights (95.8 vs. 73.1%; p < 0.001). Patients who stayed ≥ 2 midnights reported lower patient-reported outcome scores at all time-periods (preoperatively, 3 months and 1 year), but these differences did not exceed the minimum clinically important difference. Mean improvement preoperatively to 1 year postoperatively in KOOS, JR (22.53 vs. 25.89; p < 0.001), and VR-12 PCS (12.16 vs. 11.49; p = 0.002) was statistically higher for patients who stayed < 2 midnights, though these differences were not clinically significant. All-cause ED visits (p = 0.167), 90-day all-cause readmissions (p = 0.069) and revision (p = 0.277) did not statistically differ between the two cohorts. TKA patients classified as outpatient had similar quality metrics and saw similar clinical improvement following TKA with respect to most patient reported outcome measures, although they were demographically different. Outpatient classification is more likely to be assigned to younger males with higher functional scores, lower BMI, CCI, and ASA class compared with inpatients. This Retrospective Cohort Study shows level III evidence.
Keywords: outpatient arthroplasty; total knee arthroplasty; patient reported outcomes; Medicare